Private sector involvement in the euro : the power of ideas - Collignon, Stefan, 1951-; Schwarzer, Daniela (London ; New York : Routledge, 2003)
This book looks at the role of the Association for Monetary Union in Europe's role in the construction of the Euro.
Book Cover; Title; Contents; Illustrations; Acknowledgements; Abbreviations; Introduction: public consensus and EMU; Foundations; A common or a single currency?; The crises and the Phoenix; Campaigning for EMU; Epilogue; Introduction; The crises and the Phoenix; Campaigning for EMU; List of interviewees; List of expert groups; List of former AMUE board members; Notes; Bibliography; Name index; Subject index.
Includes bibliographical references (pages 242-251) and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Economic and Monetary Union; Economic and Monetary Union; Euro; Monetary unions -- European Union countries; Monetary policy -- European Union countries; Non-governmental organizations; Euro (Monnaie); Unions monétaires -- Pays de l'Union européenne.; Politique monétaire -- Pays de l'Union européenne.; Organisations non gouvernementales; BUSINESS & ECONOMICS -- Money & Monetary Policy; Euro; Monetary policy; Monetary unions; Non-governmental organizations; European Union countries